Implementasi Prinsip Appeal, Exaggeration, dan Squash & Strecth dalam Video Animasi Edukasi Gizi : “MIGI : Makan Minum Bergizi” - Yanuar Aldi Allesandro; Rahmat Maulana Sihotang; Rinda Aunillah Sirait; Pandu Watu Alam (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Nutritional issues in Indonesia continue to pose a significant public health challenge and necessitate early educational interventions. Children aged 7 to 9, categorized as part of Generation Alpha, are digital natives who are beginning to develop logical thinking abilities and demonstrate a strong preference for audiovisual content. In response, a two-dimensional digital animation entitled “MIGI: Makan Minum Bergizi” was developed as an educational medium. This project aims to implement the animation principles of appeal, exaggeration, and squash & stretch, which serve as the foundation for communication and visual quality in animation. The animation was produced using Adobe After Effects with the keyframe animation technique, resulting in the application of the appeal principle through uniquely simple internal organ character designs, bright and contrasting color palettes, and the use of symbolic language relevant to the target audience. The exaggeration principle was applied to dramatize movement and emotional shifts, while squash & stretch was implemented using scale transformation and puppet tools, maintaining volume consistency. These three animation principles were consciously and conceptually applied to enhance the visual appeal and communicative effectiveness of the educational message, making the work an engaging and potentially impactful learning medium.